Ramp lesion of the medial meniscus. Issue 5 (May 2021) - Qalib, Yusuf Omar; Tang, Yicun; Wang, Dawei; Xing, Baizhou; Xu, Xingming; Lu, Huading
Abstract : Ramp lesion of the medial meniscus used to be completely disregarded in the past. Ramp lesion has been now put under the spotlight by orthopaedic and sport medicine surgeons and requires attention. It is closely associated with anterior cruciate ligament injury. Major risk factors include chronic laxity, lateral meniscal lesion, anterior cruciate ligament reconstruction revision, anterolateral ligament tear concomitant with anterior cruciate ligament injury, time from injury, pre-operative side-to-side laxity > 6 mm, age < 30 years old, male sex, etc. Radiologists attempt to create diagnostic criteria for ramp lesion using magnetic resonance imaging. However, the only definite method to diagnose ramp lesion is still arthroscopy. Various techniques exist, among which posteromedial approach is the most highly recommended. Various treatment options are available. The success rate of ramp repair is very high. Major complications are uncommon. Cite this article: EFORT Open Rev 2021;6:372-379. DOI: 10.1302/2058-5241.6.200126